Complexities, capacities, communities : changing development narratives in early childhood education, care and development - Pence, Alan R., 1948-; Benner, Allison; University of Victoria (B.C.); BC Open Textbook Project; BCcampus (University of Victoria, 2015)
"The term 'capacity building' has come into common usage in twenty-first century international development. While the term means different things to different people, it is often used to describe an infusion of knowledge or skills to help 'build' a government's or institution's ability to address key development challenges. However, like other well intentioned interventions from the industrialized West, such 'capacity building' can have destructive, as well as productive, impacts. This volume problematizes such activities and presents an alternative approach to promoting capacity in development contexts. The volume starts with an exploration of the concept of capacity building and goes on to focus on two examples of capacity promotion for early childhood education, care and development (ECD). The First Nations Partnerships Program (FNPP), an innovative and successful post-secondary education program initiated in 1989 at the request of a large tribal council in northern Canada, led to 10 educational deliveries with diverse Indigenous communities over the subsequent two decades. The second program, launched in 1994 at the request of UNICEF headquarters, focuses on sub-Saharan Africa. While the program encompasses a range of capacity-promoting activities, the central vehicle for this ECD development work is the Early Childhood Development Virtual University (ECDVU), a program created in 2001 and now in transition to African universities. This book describes approaches to capacity promotion that respond to the complexities and possibilities of communities-at local and country levels. These initiatives challenge established developmental narratives in ECD and international development, and in so doing provide alternative ways for scholars and practitioners in ECD, education, and the broad international development field to enhance capacities"--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references and index.
Keywords: Child development; Early childhood education; Child care; Electronic books